A new decade awaits sticky platelet syndrome: where are we now, how do we manage and what are the complications?. Issue 1 (2nd January 2022) - Stasko, Jan; Holly, Pavol; Kubisz, Peter
ABSTRACT: Introduction: Sticky platelet syndrome is a less known platelet function disorder with a familiar occurrence and likely genetic background. Clinically, it is characterized by an increased risk of venous and arterial thromboembolic events and obstetric placenta-mediated complications. The increased aggregation after low-dose ADP and/or epinephrine is its distinctive laboratory feature. Though described for almost 40 years, several issues regarding its etiology, involved pathomechanisms, genetic background, optimal diagnostic and treatment approach remain controversial. Areas covered: The work aims to summarize published studies, the actual definition of the syndrome, and point out its drawbacks. A literature search on Medline, Embase, and archives from EHA congresses was performed (terms: 'sticky platelet syndrome' – 'platelet hyperreactivity' – 'platelet hyperaggregability'). The authors added in their unpublished data. The introductory overview of the present understanding is followed by the discussion of the pathophysiologic, diagnostic, and therapeutic problems. Expert Opinion: Despite the growing evidence provided by case reports and series, the lack of robust studies limits the decision-making on diagnostics and management. The diagnostic issues, particularly the standardization of light transmission aggregometry, represent the crucial problem for the broader acceptance of the syndrome. PLAIN LANGUAGE SUMMARY: Sticky platelet syndrome is aplatelet function disorder. It is associated with an increased risk of venous thromboembolism, arterial thrombosis, and obstetric placenta-mediated complications. Increased aggregation after low-dose ADP and/or epinephrine is the defining laboratory feature. Furthermore, afew studies report the familiar occurrence with possible genetic background. Several issues regarding the syndrome remain controversial: its exact etiology, genetics, optimal diagnostic, and treatment approach. These uncertainties provide ground for debate of the syndrome as aunique clinical entity. The review has two goals. Firstly, it summarizes the published studies and the actual definition of the syndrome. Secondly, it tries to point out the open pathophysiologic, diagnostic, and therapeutic problems.